The datapreneurs : the promise of AI and the creators building our future - Muglia, Bob; Hamm, Steve (Ascent Audio, 2023)
A leader in the data economy explains how we arrived at AI-and how we can navigate its future. In The Datapreneurs, Bob Muglia helps us understand how innovation in data and information technology have led us to AI-and how this technology must shape our future. The long-time Microsoft executive, former CEO of Snowflake, and current tech investor maps the evolution of the modern data stack and how it has helped build today's economy and society. And he explains how humanity must create a new social contract for the artificial general intelligence (AGI)-autonomous machines intelligent as people-that he expects to arrive in less than a decade. Muglia details his personal experience in the foundational years of computing and data analytics, including with Bill Gates and Sam Altman, the CEO of OpenAI, the creator of ChatGPT, and others that are not household names-yet. He builds upon Isaac Asimov's Laws of Robotics to explore the moral, ethical, and legal implications of today's smart machines, and how a combination of human and machine intelligence could create an era of progress and prosperity where all the people on Earth can have what they need and want without destroying our natural environment.